The frequency of antenatal care visits in the covid-19 pandemic era and new normal at Ngaglik Public Health Centre Sleman Yogyakarta Indonesia - Enny Fitriahadi; Istri Utami; Deccy Nopiyana; Luluk Rosida (International Journal of Health Science and Technology, 2022)
The worst antenatal care visits resulting risks and complications of pregnancy are not detected early, antenatal visits at least 4 times is one effort to reduce complications related to pregnancy, childbirth, and postpartum in mothers and newborns. Research objective: there is a relationship between education and ANC frequency during Covid-19 pandemic and new normal at the Ngaglik Public Health Centre Sleman Yogyakarta Indonesia. Factors that affect the reduction in ANC frequency during the pandemic are lack of information about Covid, fear of contracting it, PSBB. This research uses descriptive Correlative research method with cross sectional approach. The sample used in this study is cluster sampling with a sample of 40 respondents. The statistical test used in this study is chi square statistical test. The results obtained Univariate analysis found that the majority of Gravida 2 was 18 (45%), the majority of high school education was 23 (57.5%) and ANC visits were in the good category 4x 25 (62.5%), while the bivariate analysis stated that education with ANC visits had p-value 0.012 means p-value alpha that is 0.012 0.05 which means that Ho is rejected and Ha is accepted with the conclusion that there is a correlation between education and ANC visit.